Designing and developing OM research – from concept to publication. Issue 9 (21st February 2018) - Caniato, Federico; Doran, Des; Sousa, Rui; Boer, Harry
Abstract : Purpose: The purpose of this paper is to identify similarities and differences between qualitative-based and quantitative-based research, and to present recommendations for designing and conducting the research so that the possibilities of publishing it in leading Operations Management (OM) journals are improved. Design/methodology/approach: The paper takes its outset in contributions made at the 2016 European Operations Management Association Young Scholars Workshop. The theme of the workshop was "Designing and developing research projects in Operations Management – from concept to publication." Taking the perspectives of the case researcher, the survey researcher and the editor/reviewer, the authors present and discuss the views on and experiences with designing research for publication. Findings: The authors identify a number of recommendations that researchers should use when designing, conducting, and presenting their research for publication. The recommendations include the need to clearly and concisely establish relevance, account for choice of methodology as well as the operationalization, sampling, analytical, and validation methods used, and demonstrate the contribution of the paper in the discussion section. Furthermore, the authors draw attention to the importance of developing a publication strategy as early as possible. Other important aspects include the title of the paper, keywords selection, and rejection criteria. Finally, the authors stress the importance of "total quality management" in designing and executing OM research. Originality/value: Going beyond the standard author guidelines found at journal web sites, the authors present a collection of viewpoints, which are based on the authors' experiences as reviewers, editors, and evaluators of OM research projects and their designs.